2018
DOI: 10.1002/nbm.4023
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of listeria rhombencephalitis in small ruminants by 1H high‐resolution magic angle spinning NMR spectroscopy

Abstract: Listeria rhombencephalitis is caused by infection with Listeria monocytogenes and is associated with a high mortality rate in humans and ruminants. Little is known about the metabolic changes associated with neurolisteriosis in particular and infectious central nervous system (CNS) diseases in general. The purpose of our study was to investigate the metabolic changes associated with listeria rhombencephalitis in small ruminants (goats and sheep) as a model for inflammatory CNS disease by 1H high‐resolution mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…In accordance with previous studies [7,13], we observed relatively increased concentrations of NAAG and mIns in the brainstem compared to the thalamus, and NAA and PC in the thalamus compared to the brainstem in both in vivo-and postmortemharvested samples, underlining the importance of the differences in the metabolic profiles of brain regions.…”
Section: Regional Differences In the Metabolic Profilesupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with previous studies [7,13], we observed relatively increased concentrations of NAAG and mIns in the brainstem compared to the thalamus, and NAA and PC in the thalamus compared to the brainstem in both in vivo-and postmortemharvested samples, underlining the importance of the differences in the metabolic profiles of brain regions.…”
Section: Regional Differences In the Metabolic Profilesupporting
confidence: 92%
“…Within 3 min after the insertion of the biopsy needle the biopsy was snap frozen in liquid nitrogen and stored at −80 • C. Up to 4 biopsies were taken at each target by turning the needle clockwise and obtaining a biopsy at positions 0 • , 90 • , 180 • and 240 • . As the goats served as the control group in another study [13], only one of the biopsies was used for this study. The goats were euthanized immediately after in vivo biopsy using pentobarbitalum (Euthasol ® , Virbac AG, Switzerland, dosage: 400 mg/kg intravenously).…”
Section: Brain Biopsies and Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an early study, L. monocytogenes strain 511 was injected into the lips of goats, and this resulted in circling and other neurological signs; however, the infection was lethal for most of the animals ( 50 ). More recently, the Oevermann group has done elegant studies of rhombencephalitis in sheep and cows ( 20 , 51 53 ), but work with large animals is expensive, and these model systems lack the extensive mutant and transgenic tools available for the study of host responses to infection in mice. Another group inoculated low doses of strain EGD into the middle ear of gerbils, causing a persistent otitis media that eventually led to brain infection ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…This infection can lead to different clinical symptoms such as gastroenteritis with high fever, mastitis, encephalitis, septicemia and abortion (3,20). Encephalitic listeriosis caused by only species-L. monocytogenes is more common especially in small ruminants and has high mortality rates (1,37). Sheep are more sensitive to listeriosis than cattle (9).…”
Section: Introductionmentioning
confidence: 99%